Tool fabrication for composite forming of aircraft winglet using multi-point dieless forming - Park, Ji-Woo; Ku, Tae-Wan; Kim, Jeong; Kim, Kwang-Ho; Kang, Beom-Soo (Journal of mechanical science and technology, 2016)
Flexible forming technology such as Multi-point dieless forming (MDF) has benefits for the sheet metal field because it can implement a variety of mold shapes using a single apparatus. Generally, aircraft winglets are fabricated using composite materials. To make composite material, a curing process is needed. Therefore, it is necessary to manufacture the mold for the curing process in the fabrication composite materials. For mold manufacturing, MDF technology has the advantages of low manufacturing cost and high uniformity in mold thickness compared with conventional machining processes. In this study, numerical simulations are carried out to evaluate the feasibility of MDF process for the production of winglet molds. The objective surface is bigger than actual MDF apparatus; it is divided into 8 segments to match the dimensions of the apparatus. Experiments are conducted under the same conditions as a numerical simulation. To confirm the forming accuracy, curvature profiles of simulation and experiment results are compared with the target curvature. Eight formed segments are assembled into one winglet mold. As a result, the applicability of the MDF process to the fabrication of aircraft winglet molds is verified through this research.